Additions to the fauna of plume moths (Lepidoptera, Pterophoridae) of Uganda - Ustjuzhanin, Petr; Kovtunovich, Vasily; Anikin, Vasily; Aarvik, Leif (Zootaxa, 2016)
An overview of 20 Pterophoridae species from Uganda is given. Three of them are described as new to science: Crassuncus agassizi Ustjuzhanin & Kovtunovich sp. nov., Hellinsia anikini Ustjuzhanin & Kovtunovich sp. nov. and Hellinsia nawrothi Ustjuzhanin & Kovtunovich sp. nov. Twelve species are recorded as new to the fauna of Uganda.